Nursing diagnosis "Terminality Syndrome": a content analysis - Daniel Espirito Santo da Silva; Rosimere Ferreira Santana; Marcos Venícios de Oliveira Lopes; Dayana Medeiros do Amaral Passarelles; Antônia Rios Almeida (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to validate the nursing diagnosis "Terminality Syndrome" with experts. Methods: a quantitative research of content validation type based on collective wisdom approach. An online semi-structured questionnaire was used as an instrument for data collection, and Content Validity Index and Wilcoxon test were used for comparing possible differences. Results: the questionnaire was answered by 89 professionals after judges' assessment in relation to the structural components of the diagnosis proposed. The mean Content Validity Index of items was above that recommended, except for title, which was ≥ 0.8. The suggestions were reviewed and accepted, being forwarded for a new analysis, reaching 83.7% of agreement among participants. Conclusions: the diagnosis' content proved to be valid by judges. With that, it is expected to contribute with a useful nursing diagnosis for nursing practice documentation in palliative care.